Neonatal form of biotin-thiamine-responsive basal ganglia disease. Clues to diagnosis - Değerliyurt, Aydan; Gündüz, Mehmet; Ceylaner, Serdar; Ünal, Özlem; Ünal, Sevim (The Turkish Journal of Pediatrics, 2019)
Biotin-thiamine-responsive basal ganglia disease is characterized by seizures, dystonia and encephalopathy attacks, with an acute-subacute onset in childhood. It causes cerebral damage especially with caudate head and putamen involvement and may lead to severe sequelae and even death if left untreated. We report a patient with the neonatal form of biotin-thiamine-responsive basal ganglia disease who presented with encephalopathy and lactic acidosis in the neonatal period together with the diagnostic magnetic resonance imaging (MRI) clues. MRI in the neonatal period revealed bilateral involvement of the putamen, thalamus, and perirolandic cortical regions. However, MRI obtained at 32 months revealed involvement of the caudate nuclei in addition to the putamen and thalami. The neuroimaging findings of our patient and relevant literature indicate that patients with biotin-thiamine-responsive basal ganglia disease who are symptomatic in the neonatal period have putamen, thalami, and perirolandic cortical involvement. However, these patients do not have caudate involvement, unlike the patients who present in childhood.
Keywords: Leigh syndrome; SLC19A3; basal ganglia; biotin-thiamine-responsive basal ganglia disease; thiamine transporter 2